2017
DOI: 10.21622/resd.2017.03.2.234
|View full text |Cite
|
Sign up to set email alerts
|

The application of solar energy in agricultural systems

Abstract: -Given that one day fossil fuels will end, a need arises to find alternative fuels. Renewable energy is considered an alternative to fossil fuels and nowadays it attracts much attention. Among renewable energy sources, solar is the most important because it is available in all parts of the world. Also, this energy source is used in various industries including agriculture and it can be used in cultivating crops in the farthest corners of the world. In addition, this fuel does not cause pollution, like the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Solar radiation is the most fundamental renewable energy source [17] and the conversion of solar into chemical energy is the foundation of all agricultural production processes [18]. Solar energy is a widely used resource in agricultural applications [19] and is expected to be the most important future renewable energy source (Table 1).…”
Section: Solar Energymentioning
confidence: 99%
See 2 more Smart Citations
“…Solar radiation is the most fundamental renewable energy source [17] and the conversion of solar into chemical energy is the foundation of all agricultural production processes [18]. Solar energy is a widely used resource in agricultural applications [19] and is expected to be the most important future renewable energy source (Table 1).…”
Section: Solar Energymentioning
confidence: 99%
“…A large amount of energy can be provided by solar air/space heaters [28], [52]. Water heating systems are either natural or forced convection forms and may be either direct where water in the current collector is heated and consumed, and indirect where water is used for heating a fluid such as a water-glycol antifreeze mixture in collectors [18].…”
Section: Space and Water Heatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional poultry farming seriously consume fossil fuel and gas via the power and heating systems for heating, cooling, lighting, ventilation and running electric motors for feed lines [18,19]. Therefore, the usage of the renewable and sustainable energy technologies, including wind energy, solar energy, geothermal energy and air/water sources [20,21], plays vital role on the poultry farm owing to their potential to a reduction of energy demand and welfare losses, economy and profitability, GHG reduction and conservation of resources [22][23][24]. Hence, in this chapter, these advanced technologies is investigated and summarized for easier tracking and better understanding of energy-efficient renovation for typical poultry houses.…”
Section: Introductionmentioning
confidence: 99%
“…In paper [11], this journal discussing about the potential of using Renewable energy in Malaysia especially solar energy. In this paper [12], this paper discusses the use of solar energy in agriculture system such as to do a number of farm works, pumping water for irrigation, monitoring system and others. The research found that solar energy technologies for farming is divided into two systems which are photovoltaic cell system and uses solar capture heating system.…”
Section: Introductionmentioning
confidence: 99%